Evidence for varicose vein treatment: an overview of systematic reviews - Oliveira, Ricardo de Ávila; Mazzucca, Andréa Castro Porto; Pachito, Daniela Vianna; Riera, Rachel; Baptista-Silva, José Carlos da Costa (São Paulo Medical Journal, 2018)
BACKGROUND: Varicose veins affect nearly 30% of the world’s population. This condition is a social problem and needs interventions to improve quality of life and reduce risks. Recently, new and less invasive methods for varicose vein treatment have emerged. There is a need to define the best treatment options and to reduce the risks and costs. Since there are cosmetic implications, treatments for which effectiveness remains unproven present risks to consumers and higher costs for stakeholders. These risks and costs justify conducting an overview of systematic reviews to summarize the evidence. DESIGN AND SETTING: Overview of systematic reviews within the Discipline of Evidence-Based Health, at Universidade Federal de São Paulo (UNIFESP). METHODS: Systematic reviews on clinical or surgical treatments for varicose veins were included, with no restrictions on language or publication date. RESULTS: 51 reviews fulfilled the inclusion criteria. Outcomes and comparators were described, and a narrative review was conducted. Overall, there was no evidence that compression stockings should be recommended for patients as the initial treatment or after surgical interventions. There was low to moderate evidence that minimally invasive therapies (endovenous laser therapy, radiofrequency ablation or foam sclerotherapy) are as safe and effective as conventional surgery (ligation and stripping). Among these systematic reviews, only 18 were judged to present high quality. CONCLUSIONS: There was evidence of low to moderate quality that minimally invasive treatments, including foam sclerotherapy, laser and radiofrequency therapy are comparable to conventional surgery, regarding effectiveness and safety for treatment of varicose veins.